Overview of Antibiotic Use Patterns in Typhoid Fever Patients at the Toto Kabila Hospital Inpatient Unit in 2019 - Wilsandi Day; Rita Amini Warastuti; Ahmad Husain Palli (Journal of Health, Technology and Science (JHTS), 2021)
Typhoid fever is an acute systemic infectious disease caused by Salmonella typhi. Indonesia has a fairly high incidence with an increasing number of cases. It is estimated that there are 600,000 and 1.5 million cases of typhoid fever per year. Antibiotics are the main therapy for the treatment of typhoid fever patients. This study aims to describe the pattern of antibiotic use in typhoid fever patients in the inpatient installation of Toto Kabila Hospital in 2019. The method in this study uses descriptive statistics with the type of observational research. Data collection was carried out retrospectively. The sample was taken from the medical records of adult patients with typhoid fever who were treated at the Toto Kabila Hospital in 2019. The subject selection technique used random sampling. The subjects in this study were adult patients with typhoid fever who were treated at the Toto Kabila Hospital in 2019. The total sample obtained was 44 typhoid fever patients. The results showed that the class of antibiotics used was a third generation cephalosporin (84.1%) of the type of antibiotic ceftriaxone (72.7%) with a dose of 1 gram (72.7%) twice a day and given for 10-14 days. It can be concluded that the pattern of antibiotic use at the Toto Kabila Hospital, Gorontalo Province in 2019 was in accordance with the disease suffered.